The Role of Coriolis Force and Suspended Particles in the Fragmentation of Matter in the Central Region of Galaxy - Pensia, RK; Patidar, Ashok K; Shrivastava, V; Kumar, Vishal; Prajapat, Vikas (Journal of Bangladesh Academy of Sciences, 2012)
The role of Coriolis force and suspended particles in the fragmentation of matter in the central region of galaxy have been studied. A general dispersion relation is obtained with the help of linearized relevant magnetohydrodynamics (MHD) using normal mode analysis. It was found that an infinite homogenous viscous, permeability and suspended particles in the central region of galaxy with finite electrical resistivity and rotation is a stable system. The Coriolis force plays an important role in the central region of the galaxy. DOI: http://dx.doi.org/10.3329/jbas.v36i1.10905 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 1, 1-12, 2012